Effect of ultrasound waves against infection with giardiasis in Rattus norvegicus rats. - Asmaa Ali; Hiba Khudher (College of Education for Pure Sciences, 2018)
The present study investigated the effect of the direct ultrasonic waves, as an immune stimulator, against infection with giardiasis caused by Giardia lamblia in Norwegian rat, Rattus norvegicus. The pathological changes occurred in the rats administered orally with the cysts of G. lamblia, exposed to different durations of ultrasonic waves for 60 seconds, 150s, 210s and 240s, respectively, with constant frequency 20,000 pulsesecond(1.8w/cm2 ) were followed compared with the control group (rats administered orally with the cysts of G. lamblia, without exposure to the ultrasonic waves), along the experimental period, depending on many criteria, included the changes in cysts expel and weights of animals . The results revealed significant reduction (p>0.01) in cysts expel in the rats exposed to direct ultrasonic waves in comparison with the control group, the maximum reduction was at duration 240 seconds, and a significant elevation (p>0.01) in percentage of weights in the treated animals compared with the control group, the maximum elevation was 404. 25% , at 240 seconds .